Analisis Urgency, Seriousness, Growth (Usg) Untuk Minimalisasi Jam Berhenti Giling Pada Stasiun Gilingan Di Pt. Pg Xyz - Febby Ficha Shekina; Tranggono (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
PG XYZ is a company part of agribusiness which operates in the sugar cane agroindustry in the Sidoarjo area. PT. PG XYZ is trying to minimize the stopping hours for each mill for six months. With the Urgency, Seriousness, Growth (USG) analysis method, the causes and effects can be identified and minimized so that the company gets maximum profits in an efficient time. The sugar cane milling activity is an important part of the company's production system and has risks that have a very large impact and often occur when milling machines stop working. This is due to factors that influence the milling machine. Based on the research results, it was found that PT. PG XYZ, the biggest thing that happened and had a lot of weight was the root causes that had an impact on the machine, namely the drive engine protection device didn't work, the limit switch didn't work, the backup device was damaged, the electric motor caught fire, the oil cylinder leaked, the gearbox shaft broke. Meanwhile, for the weighting of the solution. PT. PG XYZ doubles the driving machine as a double drive, upgrades the driving machine, buys a bigger chain, adds human resources, makes spare tools. With this weighting, it is hoped that we can control stopping hours based on problem data and the most effective solutions and industrial activities run well and produce the best quality.